Relationships between nurturing care, child growth in the First 2 Years and both cognitive development and academic achievement at 10–11 Years - Tran, Lan Mai; Nguyen, Phuong Hong; Ramakrishnan, Usha; Young, Melissa F. (Elsevier, 2024)
Objectives: Nurturing Care (NC) and growth during early childhood are critical for human capital formation, but less is known about the patterns and role of NC. We used data from a Vietnamese birth cohort to identify trajectories of NC and growth in early childhood and evaluate their associations with cognitive development and academic achievement in early adolescence.